DECLARATIVE AND IMPERATIVE MOOD IN LIR-ILIR SONG - Nur, Azadat Wiqoyatin; Ulya, Najwa Laili Fathul; Indriyani, Elma; Ramadhani, Lathifa Faza (Universitas Suryakancana, 2024)
Javanese songs as a traditional literary art that are currently very close to the lives of Javanese people are becoming less and less popular. Since that time, the popularity of traditional songs began to be replaced by modern songs. Preserving these traditional songs is crucial because they hold significant cultural and emotional value. The Lir-Ilir song is a traditional song created by Sunan Kalijaga as part of the effort to spread Islam in Java in the early 16th century. This research aimed to understand the interpersonal meaning and identify mood types of the Lir-Ilir song. The research was conducted using a qualitative method, which explains the research results with description and not with statistics. Therefore, The results showed that there were two types of mood, namely declarative and imperative, and 50% declarative mood and 50% imperative mood were found. This showed that the songwriter gave a combination of statements and commands, which meant that this song gave a message and invited listeners to take action according to the message of the song.